2007
DOI: 10.1007/s11010-007-9485-7
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage inflammatory protein-1α (MIP-1α) enhances a receptor activator of nuclear factor κB ligand (RANKL) expression in mouse bone marrow stromal cells and osteoblasts through MAPK and PI3K/Akt pathways

Abstract: Osteolytic lesions are rapidly progressive during the terminal stages of myeloma, and the bone pain or bone fracture that occurs at these lesions decreases the patients' quality of life to a notable degree. In relation to the etiology of this bone destruction, it has been reported recently that MIP-1alpha, produced in large amounts in myeloma patients, acts indirectly on osteoclastic precursor cells, and activates osteoclasts by way of bone-marrow stromal cells or osteoblasts, although the details of this proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 22 publications
4
54
0
2
Order By: Relevance
“…It strongly correlates with osteolytic burden in MM [57][58][59]. Indeed, CCL3 by binding two receptors, CCR1 and CCR5, potently stimulates OC differentiation mediating the fusion of precursor cells into active mature OCs and upregulating RANKL expression by OBs [60][61][62]. CCL3 is also responsible for increased angiogenesis, tumor cell migration to the BM and tumor cell growth [7,63].…”
Section: Pathogenesis Of Osteoblast Inhibition In MMmentioning
confidence: 99%
“…It strongly correlates with osteolytic burden in MM [57][58][59]. Indeed, CCL3 by binding two receptors, CCR1 and CCR5, potently stimulates OC differentiation mediating the fusion of precursor cells into active mature OCs and upregulating RANKL expression by OBs [60][61][62]. CCL3 is also responsible for increased angiogenesis, tumor cell migration to the BM and tumor cell growth [7,63].…”
Section: Pathogenesis Of Osteoblast Inhibition In MMmentioning
confidence: 99%
“…This chemokine may also directly act on mature osteoclasts, and in a murine model, MlP-lahas been shown to increase osteoclast motility, although it did not alter osteoclast bone resorbing activity, adhesion, or survival (Yu et al, 2004). MlP-la may also act indirectly on these cells by stimulating RANKL production (Tsubaki et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…MIP-la is produced by myeloma cells, and is known to stimulate osteoclast formation and bone resorption (Choi et al, 2000). Interestingly, it has been shown that MIP-la directly affects cell signaling pathways like activation of AKT/protein kinase B, and the MAPK pathway in myeloma cells through CCR5; mediating growth, survival and migration of myeloma cells (Tsubaki et al, 2007). However, it has not yet been shown if MIP-la is capable of inducing the same survival effects in human osteoclasts.…”
Section: Effect On Osteoclasts Upon Stimulation With Mlp-lamentioning
confidence: 99%
“…MIP-1 binds to several chemokine (c-c motif) G-protein-coupled receptors including CCR1, CCR5 and CCR9, which are expressed in lymphocytes and monocytes/macrophages. It activates several signaling pathways, including PI3K, PLC, PKC, MAP kinase and JAK/STAT pathways (Tsubaki et al, 2007). MIP-1 can potently inhibit the binding of HIV to CCR5 on macrophages (Baba et al, 1999;Maurer & von, 2004).…”
Section: Macrophage Inflammatory Protein-1 Alpha (Mip-1α)mentioning
confidence: 99%
“…The mechanisms by which MIP-1 induces osteoclastic bone resorption are controversial. One study demonstrated that a RANKL-dependent pathway was responsible for activation of osteoclasts (Tsubaki et al, 2007). MIP-1 enhances RANKL expression in mouse bone marrow stromal cells and osteoblasts through the MAPK and PI3K/Akt signaling pathways.…”
Section: Macrophage Inflammatory Protein-1 Alpha (Mip-1α)mentioning
confidence: 99%